The Development of Piezoelectric Tiles for Efficient Energy Harvesting - Mohamad Ariffin, Muhammad Luqmanulhakim; Saiman, Suhaimi (Evolution in Electrical and Electronic Engineering, 2025)
This project outlines the design and development of an interactive piezoelectric tile system aimed at harvesting mechanical energy generated by footstep impacts and converting it into usable electrical energy. A prototype was developed utilising 20 piezoelectric ceramic discs, each with a diameter of 25 mm, configured in a series-parallel arrangement. In a controlled laboratory environment, the tiles were exposed to simulated foot pressure, resulting in the generation of AC voltage. This voltage was then rectified utilising a full-bridge rectifier made up of 1N4148 diodes. The output was stabilised and buffered with a 2.7 V, 0.8 F supercapacitor prior to being elevated to 5 V through a CE8301-based DC-DC converter. A regulated voltage was employed to partially charge a 3.7 V, 1200 mAh lithium-ion battery utilising a TP4056 charging module. Experimental testing evaluated three damper configurations such as spring-mounted, soft pad, and hard pad to determine their impact on output performance. The spring-mounted damper demonstrated superior performance compared to the alternatives, reaching maximum outputs of 3.72 V (AC) and 2.45 V (DC) during repeated steps. According to the measurements of current and voltage, each footstep produced around 26.75 µWh of energy. The total number of steps required to achieve a complete battery charge was estimated at 168,820, which corresponds to approximately 23.5 hours of uninterrupted stepping at intervals of 0.5 seconds. Upon complete charging with a DC power supply, the battery operated a 5W LED lamp for an estimated duration of 53 minutes. Simulations using MATLAB were performed on essential circuit stages, particularly the rectifier and boost converter, to assess their performance across different input conditions. The findings showed a strong correlation with the physical tests, with slight variations explained by diode voltage drops and inconsistent mechanical input. This investigation validates the practicality of combining piezoelectric energy harvesting with power conditioning and storage systems. The system, although not fully optimised for independent operation at this stage, exhibits significant promise for future implementation in public areas as engaging and sustainable energy alternatives.